Adoption by lesbians and gay men a new dimension in family diversity - Brodzinsky, David; Pertman, Adam. (New York ; Oxford : Oxford University Press, 2011)
This is an examination of the misconceptions, myths, research and practice literature related tosexual-minority individuals' efforts to adopt and raise children. It also provides a blueprint for research and professional training and highlights best practice standards for working with this group of adoptive parents.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Gay adoption -- United States; Gay parents -- United States; Lesbian mothers -- United States